FLORISTIC STUDY OF MEKONGGA PROTECTED FOREST: TOWARDS ESTABLISHMENT OF THE MEKONGGA NATIONAL PARK - Elizabeth Anita Widjaja; Daniel Potter (Research Center for Biology, 2014)
Mekongga is one of the highest mountains in Southeast Sulawesi. The Mekongga region was declared as protected forest in 1994, after logging had been done in this area. A floristic study of this forest was conducted from 2009 through 2011 by visiting the area twice a year, once each during the dry and wet seasons, and collecting specimens from the flowering and fruiting plants. Other species were also recorded, but most of them cannot be identified because the plants were too young or were not in flower or fruit at the time of collection. Specimens of 855 species in 155 families were collected, of which 5% (44 species) are endemic to Sulawesi and 11% (91 species) are introduced species from China, South America, India, or even Madagascar. In addition, new records for Sulawesi were collected from Mekongga for species originally recorded from Java (50 species), Malaysia (35 species), the Philippines (28 species), New Guinea (14 species), Sumatera (13 species), Borneo (11 species), Moluccas (4 species), and the Lesser Sunda Islands (3 species). Based on these data, it seems that species have mostly migrated to Mekongga from Java, then from Malaysia and the Philippines. More than 10 new species are proposed from this area, including a bamboo (Poaceae) and members of the families Orchidaceae, Gesneriaceae, Melastomataceae, Myrtaceae, and Araliaceae. Further study of the floristic account will be done, which can be used as baseline data in support of an important proposal to designate the Mekongga area as a national park.